Changes in the dielectric constant of interphase volume in polyimide–ceramic nanocomposites: A power law model approach. Issue 6 (1st September 2021) - Lay, Makara; Meng, Sopheak; Ismail, Hanafi; Huat, Tan Soon; Todo, Mitsugu
Abstract: The interphase properties in nanocomposites indicate the interaction between filler and matrix, which is dependent on the preparation method, shape, and size of filler and the chemical interaction between two phases. Local chemical environment in polymer matrix give rise to the different dielectric properties compared to that of bulk material. These properties allow the understanding of their effects on the dielectric properties and glass transition (Tg ) of the nanocomposites. In this study, interphase power law model was used to predict the interphase properties based on the experimental dielectric constant of polyimide (PI) with BaTiO3, TiO2, and ZrO2 nanocomposites. They were prepared via in situ polymerization of PI whose dielectric constant were increased at interphase filler volume fraction of BaTiO3, TiO2, and ZrO2 at 3.8, 2.05, and 1.7, respectively. These results indicate that PI/ceramics nanocomposites had poor dispersion and weak interphase interaction between the filler and the matrix, as an evidence of scanning electron microscopy and Fourier transform infrared spectroscopy results. However, PI incorporated with high aspect ratio of BaTiO3 nanofiber shows better dispersion than nanocomposites of TiO2 and ZrO2 filled PI; therefore provide higher dielectric constant and Tg . Abstract :